Upaya Meningkatkan Hubungan Sosial Siswa melalui Layanan Bimbingan Kelompok: Efforts to Improve Student Social Relations through Group Guidance Services - Mimi Suriatie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study is to obtain empirical data about improving social relations through group guidance services. The research plan used in this study was pre-experimental research using the pretest-posttest. The population in this study were students of class XI IPS, and the sampling technique used in this study was purposive sampling. The sample in this study were students who reflected a low level of social relations compared to other students, namely ten students — the method of power collection in this study using a questionnaire with a Likert scale. Before obtaining group guidance services, the level of social relations of students was in the low category with a percentage score of 486 with low criteria. Whereas after obtaining guidance services for social relations groups students receive an average rating of 812 with high standards. From the t-test obtained (t) count of 21.44 and the value (t) of the table at a significant level of 5% and N-1 (10-1) = 9 obtained (t) table of 2.262 thus, it can be concluded that group guidance services can improve student social relations. the conclusion is that there is a significant increase in students' social relationships after being given group guidance services